Subscales of the Barratt Impulsiveness Scale differentially relate to the Big Five factors of personality. Issue 3 (18th April 2017) - Lange, Florian; Wagner, Adina; Müller, Astrid; Eggert, Frank
Abstract : The place of impulsiveness in multidimensional personality frameworks is still unclear. In particular, no consensus has yet been reached with regard to the relation of impulsiveness to Neuroticism and Extraversion. We aim to contribute to a clearer understanding of these relationships by accounting for the multidimensional structure of impulsiveness. In three independent studies, we related the subscales of the Barratt Impulsiveness Scale (BIS) to the Big Five factors of personality. Study 1 investigated the associations between the BIS subscales and the Big Five factors as measured by the NEO Five‐Factor Inventory (NEO‐FFI) in a student sample ( N = 113). Selective positive correlations emerged between motor impulsiveness and Extraversion and between attentional impulsiveness and Neuroticism. This pattern of results was replicated in Study 2 ( N = 132) using a 10‐item short version of the Big Five Inventory. In Study 3, we analyzed BIS and NEO‐FFI data obtained from a sample of patients with pathological buying ( N = 68). In these patients, the relationship between motor impulsiveness and Extraversion was significantly weakened when compared to the non‐clinical samples. At the same time, the relationship between attentional impulsiveness and Neuroticism was substantially stronger in the clinical sample. Our studies highlight the utility of the BIS subscales for clarifying the relationship between impulsiveness and the Big Five personality factors. We conclude that impulsiveness might occupy multiple places in multidimensional personality frameworks, which need to be specified to improve the interpretability of impulsiveness scales.